Sodium-ion battery hard carbon negative electrode material and preparation method thereof
By using phenol and/or amine-modified phenolic resin with polycyclic aromatic structure and spherical treatment and size regulation, the problem of low true density and compaction density of the hard carbon anode material of sodium ion battery is solved, and the high true density and compaction density of the material are achieved, which improves cycle stability and electrochemical performance.
Patent Information
- Application Number
- CN202510005933.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-11
AI Technical Summary
The true density and compaction density of existing sodium ion battery hard carbon anode materials are relatively low, which limits the volume energy density of the battery cell and the industrial application of sodium ion batteries.
Phenol and/or amine-modified phenolic resin with polycyclic aromatic structure is used as the hard carbon precursor, and the true density and compaction density of the material are improved through spherical treatment and fine dimensional regulation.
The true density and compaction density of the hard carbon anode material of sodium ion battery are significantly improved, and the cycle stability and electrochemical performance of the material are improved.
Smart Images

Figure BDA0005226857620000051
Abstract
Description
Technical Field
[0001] The present invention relates to the field of negative electrode materials for sodium ion batteries, and in particular to a hard carbon negative electrode material for sodium ion batteries with a high compaction density and a preparation method thereof. Background Art
[0002] As an important electrochemical energy storage device, lithium-ion batteries have been mass-produced and widely used in 3C, automobiles, and energy storage. However, as the market demand on the consumer side, especially in the field of energy storage, continues to increase, the shortage of lithium resources and the uneven global distribution have become more prominent, which has brought about high battery costs, which has largely restricted the large-scale production and use of lithium-ion batteries. Therefore, it is imperative to find new energy storage devices to replace lithium-ion batteries.
[0003] Sodium-ion batteries work on the same principle as lithium-ion batteries, both of which are rocking-chair secondary batteries. At the same time, the raw materials used in sodium-ion batteries are abundant in resources, low in price, and have excellent safety performance, so they are likely to be favored by researchers as the next generation of new energy storage devices, and they also have great potential in large-scale energy storage scenarios such as smart grids.
[0004] The negative electrode material is one of the key components of secondary batteries. The hard carbon material used in sodium-ion batteries is a short-range disordered and long-range ordered carbon material. Compared with graphite, the graphene sheets of hard carbon are curled and disordered, the microcrystals are disordered and rich in ultra-micro pores, and have a higher theoretical capacity than graphite, but reduce the true density and compaction density of the material, thereby reducing the volume energy density of the battery cell and limiting the industrial application of sodium-ion batteries.
[0005] The prior art discloses methods for improving the compaction density of materials, such as CN117361496A mechanically shaping hard carbon to reduce the surface angles of particles to improve the compaction density, and CN118136781A modifies and lubricates the surface of hard carbon, and reduces the friction between hard carbon particles during rolling, which is more conducive to improving the compaction density. However, the prior art has limited improvement in compaction density, and has not yet designed materials from the perspective of true density. Therefore, it is necessary to provide a method for improving the compaction density of materials. Summary of the invention
[0006] In view of the problems existing in the prior art, the purpose of the present invention is to provide a hard carbon negative electrode material for a sodium ion battery and a preparation method thereof. The preparation method uses a phenol- and / or amine-modified phenolic resin with a polycyclic aromatic structure, and spheroidizes the particles and finely controls their size. The prepared hard carbon material has a higher true density and compacted density. The sodium ion battery negative electrode material obtained by this method has excellent compacted density and cycle stability.
[0007] To achieve the above-mentioned object of the invention, the first aspect of the present invention is to provide a method for preparing a hard carbon negative electrode material for a sodium ion battery, comprising the following steps:
[0008] (1) subjecting a solvent, phenol, aldehyde, a catalyst and a modifier to polymerization reaction at a certain temperature to obtain a polymer solution;
[0009] (2) spray drying and solidifying the polymer solution obtained in step (1) to obtain a spherical hard carbon precursor;
[0010] (3) The hard carbon precursor obtained in step (2) is carbonized at high temperature to obtain a negative electrode material for a sodium ion battery.
[0011] The preparation method of the present invention, wherein in step (1), the solvent includes at least one of water, methanol, ethanol, acetone, tetrahydrofuran, carbon disulfide, toluene, and chloroform.
[0012] The preparation method of the present invention, wherein in step (1), the phenol includes one or more of phenol, cresol, meta-xylenol, o-xylenol, catechol, resorcinol, and bisphenol A.
[0013] The preparation method of the present invention, wherein in step (1), the aldehyde comprises one or more of formaldehyde, acetaldehyde, propionaldehyde, and furfural.
[0014] The preparation method of the present invention, wherein in step (1), the catalyst is aqueous ammonia with a mass fraction of 20-30wt%.
[0015] The preparation method of the present invention, wherein in step (1), the modifier is a phenol containing a polycyclic aromatic structure and / or an amine containing a polycyclic aromatic structure, preferably a phenol containing a condensed aromatic hydrocarbon and / or an amine containing a condensed aromatic hydrocarbon, including one or more of naphthol, naphthylamine, anthracenol, and anthracenamine.
[0016] The preparation method of the present invention, wherein in step (1), the molar ratio of the phenol, aldehyde and pure ammonia in the ammonia water is 1:1.0-1.5:0.05-0.3.
[0017] The preparation method of the present invention, wherein in step (1), the molar ratio of the modifier to the phenol is 0.05-0.2:1, such as 0.05:1, 0.1:1, 0.15:1 or 0.2:1.
[0018] The preparation method of the present invention, wherein in step (1), the polymerization reaction temperature is 60-120°C; for example, 60°C, 80°C, 100°C or 120°C.
[0019] The preparation method of the present invention, wherein in step (1), the polymerization reaction time is 0.5-2 hours; for example, 0.5 hours, 1 hour, 1.5 hours or 2 hours.
[0020] The preparation method of the present invention, wherein in step (1), the reaction vessel used is a hydrothermal kettle and / or a reaction kettle.
[0021] The preparation method of the present invention, wherein in step (1), the solid content of the obtained polymer solution is 10-30wt%, for example, 10wt%, 20wt%, 30wt%;
[0022] The preparation method of the present invention, wherein in step (2), the obtained polymer solution is dried and solidified in a spray dryer;
[0023] The preparation method of the present invention, wherein in step (2), the inlet temperature of the spray drying treatment is 200-210°C, for example, 200°C, 205°C, 210°C; the outlet temperature is 170-180°C, for example, 170°C, 175°C, 180°C.
[0024] The preparation method of the present invention, wherein, in step (2), the atmosphere used for spray drying is nitrogen;
[0025] In the preparation method of the present invention, in step (2), the hard carbon precursor obtained is spherical and has an average particle size of 2-15 microns.
[0026] The preparation method of the present invention, wherein in step (3), the heating rate of the high temperature carbonization process is 1-10°C per minute, for example, 1°C, 3°C, 5°C or 10°C per minute;
[0027] In the preparation method of the present invention, in step (3), the high-temperature carbonization temperature (final temperature after heating) is 1400-1600° C., and the carbonization time is 2-6 hours. For example, carbonization is performed at 1400° C., 1500° C. or 1600° C. for 2 hours, 4 hours or 6 hours.
[0028] The preparation method of the present invention, wherein in step (3), the atmosphere used is nitrogen.
[0029] The second aspect of the present invention is to provide a sodium ion battery hard carbon negative electrode material, obtained according to the above preparation method, wherein the true density of the hard carbon negative electrode material is greater than or equal to 1.6g / cm 3 .
[0030] The hard carbon negative electrode material for sodium ion batteries of the present invention has a powder compaction density of greater than or equal to 1.2 g / cm at 5 tons. 3.
[0031] The sodium ion battery hard carbon negative electrode material of the present invention has a reversible capacity of 330-352 mAh / g and a first coulombic efficiency of 88.9%-91.3% when charged and discharged at a voltage of 0-1.5 V and a current density of 0.1 C. After 1000 cycles, the capacity retention rate is greater than or equal to 98%.
[0032] The third aspect of the present invention is to provide the use of the above-mentioned sodium ion battery hard carbon negative electrode material in the preparation of sodium ion batteries.
[0033] The fourth aspect of the present invention is to provide a sodium ion battery negative electrode, which is prepared using the sodium ion battery hard carbon negative electrode material described in the present invention as a raw material.
[0034] The fifth aspect of the present invention is to provide a sodium ion battery, comprising the sodium ion battery hard carbon negative electrode material described in the present invention.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] As a commonly used hard carbon precursor, phenolic resin has a more controllable structure and greater potential for improving true density and compacted density compared to natural hard carbon precursors such as biomass and derivatives (glucose, sucrose, cellulose, lignin, etc.). The present invention uses artificial synthetic resin as a raw material to prepare a negative electrode material for a sodium ion battery, uses phenol and / or amine-modified phenolic resin with a polycyclic aromatic structure, and spheroidizes the particles and regulates their size. Compared with hard carbon materials prepared from natural precursors, the hard carbon materials are more homogeneous and stable, and are suitable for large-scale preparation of hard carbon negative electrode materials for sodium ion batteries. DETAILED DESCRIPTION
[0037] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described below, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments described herein. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art belong to the scope of protection of the present invention.
[0038] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0039] Unless otherwise specified, all reagents and raw materials used in the present invention are commercially available products or products that can be prepared by known methods.
[0040] Example 1
[0041] (1) Add phenol, formaldehyde solution and ammonia water (20 wt%) to 1 liter of ethanol, the molar ratio of phenol, formaldehyde and ammonia is 1:1.3:0.1; add naphthol as a modifier to the solution, the molar ratio of the modifier to phenol is 0.2:1. The mixed solution is reacted in a 5 liter reactor at 80°C for 2 hours to obtain a polymer solution with a total solid content of 30 wt%;
[0042] (2) spray drying and curing the polymer solution obtained in step (1) in a nitrogen atmosphere. The spray drying inlet temperature is 210°C, the outlet temperature is 180°C, and the feed rate is 90 ml / min to obtain a spherical hard carbon precursor with an average particle size of 8 μm;
[0043] (3) The hard carbon precursor obtained in step (2) is carbonized at 1400° C. for 4 hours under nitrogen protection at a heating rate of 3° C. per minute to obtain a negative electrode material for a sodium ion battery.
[0044] Example 2
[0045] (1) Add phenol, formaldehyde solution and ammonia water (20 wt%) to 1 liter of ethanol, the molar ratio of phenol, formaldehyde and ammonia is 1:1.5:0.1; add naphthol as a modifier to the solution, the molar ratio of the modifier to phenol is 0.15:1. The mixed solution is reacted in a 5 liter reactor at 90°C for 2 hours to obtain a polymer solution with a total solid content of 30 wt%;
[0046] (2) spray drying and curing the polymer solution obtained in step (1) in a nitrogen atmosphere. The spray drying inlet temperature is 210°C, the outlet temperature is 180°C, and the feed rate is 80 ml / min to obtain a spherical hard carbon precursor with an average particle size of 7 μm;
[0047] (3) The hard carbon precursor obtained in step (2) is carbonized at 1600° C. for 2 hours under nitrogen protection at a heating rate of 3° C. per minute to obtain a negative electrode material for a sodium ion battery.
[0048] Example 3
[0049] (1) Add phenol, formaldehyde solution and ammonia water (25 wt%) to 1 liter of ethanol, the molar ratio of phenol, formaldehyde and ammonia is 1:1.1:0.1; add anthracene phenol as a modifier to the solution, the molar ratio of the modifier to phenol is 0.2:1. The mixed solution is reacted in a 5 liter reactor at 80°C for 1.5 hours to obtain a polymer solution with a total solid content of 30 wt%;
[0050] (2) spray drying and curing the polymer solution obtained in step (1) in a nitrogen atmosphere. The spray drying inlet temperature is 200°C, the outlet temperature is 180°C, and the feed rate is 80 ml / min to obtain a spherical hard carbon precursor with an average particle size of 7 μm;
[0051] (3) The hard carbon precursor obtained in step (2) is carbonized at 1500° C. for 4 hours under nitrogen protection at a heating rate of 3° C. per minute to obtain a negative electrode material for a sodium ion battery.
[0052] Example 4
[0053] Except that the modifier in step (1) is naphthylamine, the steps described in this embodiment are the same as those in Example 1.
[0054] Comparative Example 1
[0055] (1) Add phenol, formaldehyde solution and ammonia water to 1 liter of ethanol, the molar ratio of phenol, formaldehyde and ammonia is 1:1.3:0.1, and the total solid content is 30%. The mixed solution is reacted in a 5-liter reactor at 80°C for 2 hours to obtain a polymer solution;
[0056] (2) spray drying and curing the polymer solution obtained in step (1) in a nitrogen atmosphere. The spray drying inlet temperature is 210° C., the outlet temperature is 180° C., and the feed rate is 90 ml / min, to obtain a spherical hard carbon precursor with an average particle size of 8 μm;
[0057] (3) The hard carbon precursor obtained in step (2) is carbonized at 1400° C. for 4 hours under nitrogen protection at a heating rate of 3° C. per minute to obtain a negative electrode material for a sodium ion battery.
[0058] The true density and compacted density of the hard carbon materials prepared in each embodiment and comparative example tested by the true density meter and the powder compaction density meter are shown in Table 1. With the metal sodium sheet as the negative electrode and the hard carbon materials prepared in each embodiment and comparative example as the positive electrode, button cells were assembled in an argon-protected glove box, and charged and discharged at a current density of 0.1C at a voltage of 0-1.5V, and the first discharge specific capacity and reversible capacity were measured, and the first coulombic efficiency was calculated, and the capacity retention rate after 1000 times of charge and discharge at a current density of 1C was measured. The results are shown in Table 1.
[0059] Table 1
[0060]
[0061] It is found through the examples and comparative example 1 that the addition of the modifier can effectively improve the true density and compaction density of the material, while improving the reversible capacity and cycle capacity retention rate.
[0062] The embodiments and comparative examples of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.
Claims
1. A method for preparing a hard carbon negative electrode material for a sodium ion battery, characterized in that: The following steps are involved: (1) subjecting a solvent, phenol, aldehyde, a catalyst and a modifier to polymerization reaction to obtain a polymer solution; (2) drying and solidifying the polymer solution obtained in step (1) to obtain a spherical hard carbon precursor; (3) carbonizing the hard carbon precursor obtained in step (2) at high temperature to obtain a negative electrode material for a sodium ion battery; The modifier is a phenol containing a polycyclic aromatic structure and / or an amine containing a polycyclic aromatic structure.
2. The preparation method according to claim 1, characterized in that: In step (1), the solvent includes at least one of water, methanol, ethanol, acetone, tetrahydrofuran, carbon disulfide, toluene, and chloroform; and / or: the phenol includes at least one of phenol, cresol, m-xylenol, o-xylenol, catechol, resorcinol and bisphenol A; and / or: the aldehyde comprises at least one of formaldehyde, acetaldehyde, propionaldehyde and furfural; And / or: the catalyst is aqueous ammonia, preferably aqueous ammonia with a mass fraction of 20-30wt%; Preferably, the molar ratio of the phenol, aldehyde and pure ammonia in the ammonia water is 1:1.0-1.5:0.05-0.
3.
3. The preparation method according to claim 1 or 2, characterized in that: In step (1), the modifier is a phenol containing condensed aromatic hydrocarbons and / or an amine containing condensed aromatic hydrocarbons, preferably at least one of naphthol, naphthylamine, anthracenol and anthracenamine; Preferably, the molar ratio of the modifier to phenol is 0.05:1-0.2:1 Preferably, the polymerization reaction temperature is 50-120°C, preferably 60-80°C; Preferably, the polymerization reaction time is 0.5-2 hours, preferably 1-2 hours; Preferably, the solid content of the obtained polymer solution is 10-30 wt%.
4. The preparation method according to claim 1, characterized in that: In step (2), the drying is spray drying, the inlet temperature of the spray drying is 200-210°C, and the outlet temperature is 170-180°C; Preferably, the atmosphere used for the spray drying is nitrogen.
5. The preparation method according to claim 1 or 4, characterized in that: In step (2), the average particle size of the obtained spherical hard carbon precursor is 2-15 microns.
6. The preparation method according to claim 1, wherein In step (3), the high temperature carbonization temperature is 1400-1600° C., and the carbonization time is 2-6 hours; Preferably, the heating rate of the high temperature carbonization process is 1-10°C per minute; Preferably, the atmosphere used in the high temperature carbonization process is nitrogen.
7. The sodium ion battery hard carbon negative electrode material obtained according to any one of claims 1 to 6, characterized in that: The true density of the hard carbon negative electrode material is greater than or equal to 1.6 g / cm 3 The powder compaction density of the hard carbon negative electrode material under 5 tons is greater than or equal to 1.2 g / cm 3 .
8. The sodium ion battery hard carbon negative electrode material according to claim 7, characterized in that: Under a voltage of 0-1.5V and a current density of 0.1C for charging and discharging, the hard carbon negative electrode material for the sodium ion battery has a reversible capacity of 330-352mAh / g, an initial coulombic efficiency of 88.9%-91.3%, and a capacity retention rate of greater than or equal to 98% after 1000 cycles.
9. A sodium ion battery negative electrode, wherein: The sodium ion battery negative electrode is prepared using the sodium ion battery hard carbon negative electrode material obtained by the preparation method according to any one of claims 1 to 6 or the sodium ion battery negative electrode hard carbon material according to any one of claims 7 to 8 as raw material.
10. A sodium ion battery, comprising the sodium ion battery negative electrode according to claim 9.
Citation Information
Patent Citations
Sodium-ion battery hard carbon negative electrode material with high compaction density and low specific surface area and preparation method of sodium-ion battery hard carbon negative electrode material
CN117361496A
Sodium ion battery negative electrode material, preparation method thereof and vehicle
CN118136781A